The simulation appositive between the mubtada'(initial) and khabar(predicate): In the Holy Qur'an (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
This research discusses the simulation appositive between the mubtada' and khabar in the Holy Qur'an, demonstrating its concept and importance. The simulation is regarded as a tool or relation created by the language in many grammar domains to avoid the ambiguity, revealing that the inconsistency in any aspect or position of the noun phrase is an appositive created intentionally by the producer of the linguistic text in order to make a specific allowable effect. The research is divided into three sections: gender simulation, syntactic simulation, and numerical simulation. The research was built according to examples from the Holy Qur'an and to debates of some grammarians , trying to simplify the concepts as much as possible.